Systematic Literature Review of the Natural Environment of the Coromandel Peninsula, New Zealand, from a Conservation Perspective - Vladyslav Zakharovskyi; Károly Németh (Conservation, 2021)
This research presents a literature review of published scientific literature on the Coromandel Peninsula, a well-known region of the northern part of the North Island of New Zealand. It contains many biological, geological, and historical features and is well known for beautiful scenery, resulting from a volcanic rock-dominated terrestrial environment influenced by oceanic factors at the coast. All these factors have combined to make the Coromandel a popular tourism destination for New Zealanders and offshore visitors. In researching the current state of knowledge of the region, we searched three scientific databases to define the main ways of studying the region. The results demonstrated a high interest in biological and environmental factors, reflected in the type and scale of conservation measures applied to flora and fauna of the region. Additionally, specificity of geological evolution was a highly examined subject, in the context of hydrothermal alteration as related to gold and silver mineralization resulting in extensive exploration and mining. Meanwhile, indigenous cultural aspects of the land were not recognizable as expected within Western scientific literature, even though the region contains sites recognized as some of the earliest Māori habitations. Therefore, we suggest future studies to expand our understanding of scientific, cultural, and social aspects of the region as applied to the field of conservation in the region.